Örgütlerde takım çalışması ve performansa etkileri - Sümter, Esra (My University, 2003)
In a world under a globalisation phase, companies have taken their parts in the process of rapidly changing context and conditions of competition. Within this phase, changes have taken place in four major ground in the companies. In the companies these major changes have been from systems depending on managing to leadership, from individualism to team work, from customer service to partnership with the customer and traditional compensation system to appreciation and reward. Starting from this point where teamwork is essential, we may ask if there is a possibility for the relations to be in a positive way between the performance of team members and team climate. The subject of this research is surveying the relation between the team climate and performance management in the retailer companies which works with teamwork - depended systems. Totally 100 participants from 2 different companies constitute the example group of this research. In this research, the relation between every sub-exponent of team climate and performance has been examined. Depending on the outcome of the research, it has been determined that the performance of the employees who has the strong values in task orientation are higher than the others. Besides this, it has also been examined the existence of a potential significant relation between the sub-exponents of team climate and demographic variables and such a relation between the gender variables and sub-exponents of team climate has distinguished.

Küreselleşen dünyada hızla değişen ortama ve rekabet koşullarına uyum sağlayabilmek ve ayakta kalabilmek amacıyla işletmeler de bu değişim içerisindeki yerini almıştır. Bu süreç içerisinde işletmelerde dört önemli alanda değişimler meydana gelmiştir. Bunlar ; yönetimden liderliğe, bireylerden ekip çalışmasına, müşteri hizmetlerinden ortaklıklara ve geleneksel ücret sistemlerinden takdir ve ödül sistemlerine geçişin gerçekleşmesidir. Buradan yola çıkarak, başarılı işletmeler için takım çalışmasının temel alındığı günümüzde takım üyelerinin takım iklimi algısı ile yöneticilerin performans değerlendirmeleri arasında bir ilişki var mıdır ? Bu araştırmada, perakendecilik sektöründe takım çalışması uygulanan şirketlerde takım iklimi ile performans yönetimi arasındaki ilişki incelenmiştir. Araştırmanın örneklem grubunu iki ayrı firmada toplam 100 çalışan teşkil etmektedir. Araştırmada, takım ikiliminin her bir alt boyutunun performansla olan ilişkisi araştırılmıştır. Araştırma sonuçlarına dayanarak, takım iklimi boyutlarından işe yönelme boyutu algısı yüksek değerlere sahip olan çalışanların performanslarının da yüksek olduğu belirlenmiştir. Bunun yanısıra, takım ikliminin alt boyutları ile demografik değişkenler arasında anlamli bir ilişki olup olmadığı incelenmiş ve cinsiyet değişkeni ile takım iklimi boyutları arasında anlamlı bir ilişki tespit edilmiştir.
Keywords: Kamu Yönetimi